2022
DOI: 10.1111/apt.16839
|View full text |Cite
|
Sign up to set email alerts
|

Stringent screening strategy significantly reduces reactivation rates of tuberculosis in patients with inflammatory bowel disease on anti‐TNF therapy in tuberculosis endemic region

Abstract: Background: Anti-tumor necrosis factor (anti-TNF) therapy use in patients with inflammatory bowel disease (IBD) leads to an increased risk of tuberculosis (TB) reactivation despite latent tuberculosis (LTB) screening, especially in TB endemic regions. Aim:We evaluated the effect of stringent screening strategy and LTB prophylaxis on TB reactivation. Methods:We performed an ambispective comparison between patients who received anti-TNF therapy after January 2019 (late cohort) and between Jan 2005 and Jan 2019 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…We thank Selinger and colleagues for their insightful comments on our paper. 1,2 We fully agree with the points raised by them that the latent TB screening policy should be dependent on the local endemicity, and the difference in TB incidence between high and low endemic areas should direct different screening strategies. This is evident in the studies from India which have shown rates of TB reactivation as high as 11.6% following anti-TNF therapy in patients with inflammatory bowel diseases which is in direct contrast to the British audit, which did not find any case of reactivation in 360 patients.…”
Section: N V I T E D E D I T O R I a Lsupporting
confidence: 70%
See 2 more Smart Citations
“…We thank Selinger and colleagues for their insightful comments on our paper. 1,2 We fully agree with the points raised by them that the latent TB screening policy should be dependent on the local endemicity, and the difference in TB incidence between high and low endemic areas should direct different screening strategies. This is evident in the studies from India which have shown rates of TB reactivation as high as 11.6% following anti-TNF therapy in patients with inflammatory bowel diseases which is in direct contrast to the British audit, which did not find any case of reactivation in 360 patients.…”
Section: N V I T E D E D I T O R I a Lsupporting
confidence: 70%
“…We thank Selinger and colleagues for their insightful comments on our paper 1,2 . We fully agree with the points raised by them that the latent TB screening policy should be dependent on the local endemicity, and the difference in TB incidence between high and low endemic areas should direct different screening strategies.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…46 Supporting this, a recent study from India demonstrated that stringent screening for LTBI prior to anti-TNF therapy that includes clinical history, TST, LTBI, CXR and CT chest can significantly mitigate the risk of TB reactivation. 50 In this study by Kumar et al, 50 However, clinical practice varies significantly as this remains an almost evidence-free zone.…”
Section: Manag Ement Of Ib D In Tb -Endemic Countrie Smentioning
confidence: 77%
“…Following the first report of this treatment-related complication [1], several scientific societies and international organizations published guidelines for the screening and treatment of LTBI in patients receiving biological treatment [2]. The adherence to these recommendations led to a decrease, but not the complete disappearance, in the number of cases of active TB [3][4][5]. Active TB still occurs, probably due to inadequate compliance with the screening recommendations [6], the limitations of immunodiagnostic tests [7] and the occurrence of de novo infections [4].…”
Section: Introductionmentioning
confidence: 99%